The Lumumba Generation : African Bourgeoisie and Colonial Distinction in the Belgian Congo - Tödt, Daniel (2021)
How and why did the African elite turn from loyal intermediaries into opponents of the colonial state? This book wants to help better understand the dramatic political and cultural processes of decolonization in the Belgian Congo. Focusing on the making of a bourgeois African elite, the book deals with the social identity and cultural self-representations, the daily life and political activism of the so called Évolués.